2012
DOI: 10.1007/s11049-012-9179-z
|View full text |Cite
|
Sign up to set email alerts
|

Frequency biases in phonological variation

Abstract: Abstract. In the past two decades, variation has received a lot of attention in mainstream generative phonology, and several different models have been developed to account for variable phonological phenomena. However, all existing generative models of phonological variation account for the overall rate at which some process applies in a corpus, and therefore implicitly assume that all words are affected equally by a variable process. In this paper, we show that this is not the case. Many variable phenomena ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 90 publications
(77 reference statements)
6
81
0
1
Order By: Relevance
“…But crucially, the experimental results also showed that the frequency effects in tone sandhi application is regulated by grammatical factors, as evidenced by the different frequency effects Shanghai. This point echoes the position of "grammar dominance" espoused in Coetzee (2009aCoetzee ( , 2009b, Coetzee & Pater (2011), Kawahara (2011aKawahara ( , 2011b, Coetzee & Kawahara (2012), among other.…”
Section: Summary Of Findingssupporting
confidence: 57%
See 1 more Smart Citation
“…But crucially, the experimental results also showed that the frequency effects in tone sandhi application is regulated by grammatical factors, as evidenced by the different frequency effects Shanghai. This point echoes the position of "grammar dominance" espoused in Coetzee (2009aCoetzee ( , 2009b, Coetzee & Pater (2011), Kawahara (2011aKawahara ( , 2011b, Coetzee & Kawahara (2012), among other.…”
Section: Summary Of Findingssupporting
confidence: 57%
“…According to Coetzee & Pater (2011), phonological variation is "a situation in which a single morpheme can be realized in more than one phonetic form in a single environment". American English t/d-deletion (Labov, 1989;Guy, 1994;Coetzee, 2004), forms of reduplication in Ilokano (Hayes & Abad, 1989;Boersma & Hayes, 2001;Coetzee, 2006), and Japanese geminate devoicing (Coetzee & Kawahara, 2012) are all well-known examples of phonological variation. Most of the findings so far, however, have come from segmental processes.…”
Section: Background and Purposementioning
confidence: 99%
“…This question is in part motivated by a growing body of interests in to what extent lexical frequency affects phonological regularity (for different proposals on this issue, see e.g. Boersma and Hayes 2001;Bybee 1999Bybee , 2001Coetzee 2009b;Coetzee and Kawahara 2010;Coleman and Pierrehumbert 1997;Frisch et al 2000;Hay et al 2003;Hayes and Londe 2006).…”
Section: Seven Hypotheses Testedmentioning
confidence: 99%
“…Work in this vein develops formal grammatical models of how different factors condition a variable's rate of application, often to address higher-level questions such as: What the set of possible patterns of variation are for a given variable, across dialects (e.g., why is deletion rate never higher before vowels than before consonants), and why variability occurs in some contexts but not others (e.g., in codas but not in onsets, for CSD). For example, Coetzee and Kawahara (2013) propose an account for why high frequency words are more likely to undergo deletion in CSD, by weighting faithfulness constraints depending on the lexical frequency of the words involved. The idea that the effect of phonological environment external to a word (like the onset of a following word in the case of CSD) might interact with factors like pause duration and word frequency has not been explored, however, with the notable exception of Coetzee (2009), who reports that frequency does not interact with the effect of the phonological environment in an experimental test of which factors affect intuitions about the likelihood of t/d deletion.…”
mentioning
confidence: 99%